(untitled) (International Journal of Physiotherapy, 2025)
Background: Non-specific Forward Head Translation (FHT) occurs due to any cervical spine dysfunction brought on by an imbalance in the muscles surrounding the cervical spine. Any rise or decline in the Craniovertebral (CV) angle is the most prevalent abnormality associated with FHT. The majority of women who knot ponytails frequently exhibit it. Forward head position can be evaluated using a variety of techniques. The study’s objective is to assess the immediate changes in FHT and CV angle when hairs are knotted at different distances from the C7 vertebrae. Methods: Ninety-three female participants between 18 and 30 years of age participated in the observational study. All participants were assessed for changes seen in Cranio-Vertebral (CV) angle and Forward Head Translation (FHT) due to tying a ponytail in the sagittal plane. The outcome measures employed were the photogrammetry method, assisted by the AI Posture Evaluation and Correction System (APECS) app, and the Tragus to Wall Distance (TWD) test. Results: Chi-Square test was utilized to perform the data analysis, which showed statistically insignificant difference (p.>0.05) in both the outcome measures, i.e., when the hairs were tied at the top of the head, it showed more FHT and less CV angle, and when the hairs were kept open, it showed less FHT and more CV angle. Conclusion: The present observational study demonstrated an immediate effect and significant difference in FHT and CV angle when tying a ponytail at several distances from the C7 vertebrae, as measured by the TWD test and the Photogrammetry Method.